Detecção molecular de Reovírus e Rotavírus na avicultura industrial de Minas Gerais. - Renata Luci Rios (2010)
The reoviroses and rotaviroses are viroses of the Family Reoviridae. These faeces viruses most frequently detected or isolated from feces of broilers with one to four weeks of age. And are most always assiated with enteritis. Diarrhea, and general symptoms such as decreased feed conversion and weight gain, desuniformidde the lot, and culling higr mortality. In this study were analized 54 samples of feces collected from the field in the period from March 2008 to January 2010 in the main regions of the poultry industry of Minas Gerais. The samples were investigated for the presence of genome of Reovirus and Rotavirus, throught the techniques of PAGE and nested-PCR. The results indicated the presence of genome of both viruses in the samples analyzed, indicating the presence of virus in the poultry industry of Minas Gerais.